Un oso se ha perdido! - Hayles, Karen; Jones, Jenny, 1954 June 20- (Bath : Parragon, 2008)
As ten bears return home, they get lost, one by one, until there is only one lonely bear left.
Keywords: Bears -- Juvenile fiction; Osos -- Novela juvenil